1972
DOI: 10.1007/bf00036763
|View full text |Cite
|
Sign up to set email alerts
|

Breaking breeding barriers in Lycopersicon. 2. Breakdown of self-incompatibility in L. peruvianum (L.) Mill.

Abstract: Attempts were made to break the self-incompatibility in L. peruvianum by selection of mutated S-alleles through large-scale self-pollination on clones with pollen which was mutagenically treated in different stages of development . Besides self-compatibility was searched for in inbred lines .The self-incompatibility in L. peruvianum was found to be very strict indeed . From more than 22,000 self-pollinations on 5 clones 1527 seeds were obtained, seed set being very erratic . The possible causes of this seed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 44 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Thus the Phlox response is not unexpected. In moderately self-fertile plants, inbreeding often reduces the level of selffertility (Medicago sativa, Wilsie & Skory, 1948;Wilsie, 1958;Melton, 1970;Viciafaba, Drayner, 1956, 1959 Holden & Bond, 1960; Lycopersicon peruvianum, Hogenboom, 1972;Ranunculus acris, Osterbye, 1986). parent values varied from zero to 24 per cent; the mean was 9.17 per cent.…”
Section: Ytlementioning
confidence: 99%
“…Thus the Phlox response is not unexpected. In moderately self-fertile plants, inbreeding often reduces the level of selffertility (Medicago sativa, Wilsie & Skory, 1948;Wilsie, 1958;Melton, 1970;Viciafaba, Drayner, 1956, 1959 Holden & Bond, 1960; Lycopersicon peruvianum, Hogenboom, 1972;Ranunculus acris, Osterbye, 1986). parent values varied from zero to 24 per cent; the mean was 9.17 per cent.…”
Section: Ytlementioning
confidence: 99%
“…Extensive studies with radiations and chemical mutagens have shown that none generated new S-alleles (Lewis, 1949(Lewis, , 1951Lewis and Crowe 1954;Pandey, 1956Pandey, , 1965Brewbaker and Natarajan 1960;de Nettancourt and Ecochard, 1968;Hoffman, 1971;de Nettancourt, 1974, 1975), thus suggesting that new 5-specificities probably do not result from point mutations t the S-locus (see Sree Ramulu, 1980). Inbreeding, the only method which so far has generated new S-alleles ldads to some processes which result under favourable conditions in the generation of new 5-specificities (Denward, 1963;de Nettancourt and Ecochard, 1969;de Nettancourt et a!., 1971;Pandey, 1970aPandey, , 1972Pandey, , 1977Hogenboom, 1972;Anderson et al, 1974;Sree Ramulu, 1982). The S-alleles are stable under the conditions of a relatively high degree of heterozygosity and the S-allele dependent polygenic system is presumably drastically modified by inbreeding.…”
Section: Discussionmentioning
confidence: 99%
“…Segregations were tested with the aid of binomial probability paper . Material and methods not described here were described earlier (HOGENOOM, 1972) .…”
Section: Mteril Nd Methodsmentioning
confidence: 99%
“…In this paper an attempt will be made to determine the genetics of the self-compatibility which was found in Lycopersicon peruvianum (HOGENOOM, 1968(HOGENOOM, , 1972 . This study is necessary to come to an efficient use of the self-compatibility in pre-breeding of L .…”
Section: Introductionmentioning
confidence: 99%